1982
DOI: 10.1051/jphys:0198200430100147500
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural properties of iron-based oxide glasses, Fe 2O3-BaO-B2O3, from 57Fe Mössbauer spectroscopy

Abstract: 2014 La configuration électronique du fer, l'ordre structural à courte distance et les propriétés magnétiques de verres de composition (Fe2O3)x(BaO)y(B2O3)z sont établis par spectroscopie Mössbauer de 57Fe en combinaison avec des mesures macroscopiques. La coordinance moyenne du fer est déterminée par le rapport atomique Fe/O dans le milieu tandis que la configuration de valence du fer dépend principalement des conditions de préparation. Un ordre structural à courte distance très strict est mis en évidence aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…An example which may perhaps illustrate case (B) is amorphous Fe 24 Zr 76 as a mean η ≈ 0.67±0.07 and prob(V zz > 0) = 1 were reported from Mössbauer spectra recorded in applied fields [7]. A mean η ≈ 0.5 and prob(V zz > 0) = 1 were reported from Mössbauer spectra of iron-based oxide glasses Fe 2 O 3 -BaO-B 2 O 3 recorded in applied fields [58]. The models discussed above may also be useful in other fields as shown for instance by recent EPR studies of glasses [37,62].…”
Section: Statistical Invariance By Rotationmentioning
confidence: 87%
See 1 more Smart Citation
“…An example which may perhaps illustrate case (B) is amorphous Fe 24 Zr 76 as a mean η ≈ 0.67±0.07 and prob(V zz > 0) = 1 were reported from Mössbauer spectra recorded in applied fields [7]. A mean η ≈ 0.5 and prob(V zz > 0) = 1 were reported from Mössbauer spectra of iron-based oxide glasses Fe 2 O 3 -BaO-B 2 O 3 recorded in applied fields [58]. The models discussed above may also be useful in other fields as shown for instance by recent EPR studies of glasses [37,62].…”
Section: Statistical Invariance By Rotationmentioning
confidence: 87%
“…However, as solely the QS distribution associated with equation (52) was derived [58], the final result does not depend on whether V 0 is rotated or not (section 4.3). The speed at which theṼ GI contribution dominates theṼ 0 one was also investigated by varying x.…”
Section: A Simple Extension Of the Gim Modelmentioning
confidence: 91%
“…For this sample h (8.4 at % Fe), the saturated magnetic spectrum (1.4 K) is analysed in the hypothesis of an « amorphous » magnetic structure, using a fitting procedure described in detail in [10] (Fig. 6) : a " random orientation is assumed for the angle 0 between electric field gradient and hyperfine field principal axes.…”
Section: M6ssbauermentioning
confidence: 99%
“…The properties of the ternary oxide glasses, L'20-B203-Fe2o3, are inferred by combining bulk (ac-susceptibility, magnetization) and local (17 Fe Mossbauer spectroscopy) measurements. In a previous paper on the Ba0-B203-Fe203 glass systems [10] it has been shown that the magnetic properties are governed by the Fe concentration. Here, more attention is devoted to the dilute concentration range, where isolated Fe3 + ions coexist with small magnetic clusters, and to the intermediate concentration range, where the glasses exhibit a mictomagnetic transition owing to topological disorder and frustration effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation